Engineering the TetR-family transcriptional regulator XNR_0706 to enhance heterologous spinosad production in Streptomyces albus B4 chassis - Xingjun Cui; Hao Tang; Wenzong Wang; Wenping Wei; Jing Wu; Bang-Ce Ye (Synthetic and Systems Biotechnology)
The TetR family of regulators are an important group of transcription regulators that regulate diverse cellular processes in prokaryotes. In this study, we found that XNR_0706, a TetR family regulator, controlled the expression of XNR_0345, XNR_0454, XNR_0513 and XNR_1438 putatively involved in fatty acid β-oxidation by interacting with the promoter regions in Streptomyces albus B4. The transcription level of these four genes was downregulated in XNR_0706 deletion strain (ΔXNR_0706) and restored by XNR_0706 complementation in Δ0706/pIB-0706, demonstrating that XNR_0706 was a positive transcriptional regulator of the genes. With toxic long-chain fatty acids addition in TSB media, deletion of XNR_0706 caused significantly poor growth, whereas XNR_0706 complementation increased the utilization of additional fatty acids, resulting in restored growth. Fatty acid β-oxidation is one source of acetyl- and malonyl-CoA precursors for polyketides biosynthesis in actinobacteria. Overexpression of XNR_0706 in B4/spnNEW, a spinosad heterologous expression strain derived from S. albus B4, increased spinosad yield by 20.6 %. Additionally, supplement of 0.3 g/L fatty acids resulted in a further 42.4 % increase in spinosad yield. Our study reveals a regulatory mechanism in long-chain fatty acids metabolism in S. albus and these insights into the molecular regulation of β-oxidation by XNR_0706 are instrumental for increasing secondary metabolites in actinobacteria.